Consumer Perception Towards Organic Food Products in India - Abdin, Shahnawaz; Mullick, N. H.; Zargar, Zubair Hamid (Journal of Commerce and Trade, 2016)
Organic foods are those made from agricultural products grown without the use of pesticides or chemical fertilizers. The demand for environmentally friendly products like organic foods has significantly increased due to increasing awareness on health, food safety and environmental concerns. In the recent past a growing interest has been observed by different people e.g. consumers, producers, development practitioners in quality and organic foods especially vegetables, fruits and crops. Consumers’ preference for quality food taking is based on a general perception that organic foods have more desirable characteristics than conventionally-grown alternatives. Human health, food safety and environmental stewardship, along with several other product characteristics such as nutritive value, taste, freshness, appearance, and other sensory characteristics influence consumer preferences. With the growing number of diversified and complex goods, it has become difficult for ordinary and individual consumers to assess the quality of the products and get the highest value for the money spent. Consumers often feel frustrated and confused in choosing an item that would ensure the reasonable value for money. Often they are cheated and deceived in quality, weight and price by the dishonest seller. Consumer protection is no more a slogan today and it’s the concern of everyone as all citizens are consumers. While consumerism has become a strong movement and consumer organizations are highly powerful in the developed as well as in many of the developing countries, a great majority of the consumers in our country are still in the dark about their basic rights and obligations as consumers.